2017
DOI: 10.1128/aac.01709-16
|View full text |Cite
|
Sign up to set email alerts
|

Increased Costs Associated with Bloodstream Infections Caused by Multidrug-Resistant Gram-Negative Bacteria Are Due Primarily to Patients with Hospital-Acquired Infections

Abstract: The clinical and economic impacts of bloodstream infections (BSI) due to multidrug-resistant (MDR) Gram-negative 599]) groups (P ϭ 0.12). Unadjusted mean costs were 1.62 times higher in MDR than in non-MDR BSI ($59,266 versus $36,452; P ϭ 0.003). This finding persisted after adjustment for patient factors and appropriate empirical antibiotic therapy (means ratio, 1.18; 95% CI, 1.03 to 1.36; P ϭ 0.01). Adjusted analysis of patient subpopulations revealed that the increased cost of MDR BSI occurred primarily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 47 publications
2
56
1
Order By: Relevance
“…57 For example, one study found that the mean inpatient cost for MDR-E. coli was $18,917 compared with non-MDR E. coli, which was $14,776. 58 In the same study, the cost difference was greater for MDR versus non-MDR K. pneumoniae versus non-MDR with mean inpatient cost of $115,868 versus $28,877, respectively. Imipenem-resistant P. aeruginosa has been associated with an attributable cost of $85,299 compared with imipenem-susceptible P. aeruginosa.…”
Section: Health Care Burden Attributable Mortality and Costmentioning
confidence: 88%
“…57 For example, one study found that the mean inpatient cost for MDR-E. coli was $18,917 compared with non-MDR E. coli, which was $14,776. 58 In the same study, the cost difference was greater for MDR versus non-MDR K. pneumoniae versus non-MDR with mean inpatient cost of $115,868 versus $28,877, respectively. Imipenem-resistant P. aeruginosa has been associated with an attributable cost of $85,299 compared with imipenem-susceptible P. aeruginosa.…”
Section: Health Care Burden Attributable Mortality and Costmentioning
confidence: 88%
“…Regarding the site of acquisition, the bacteremia was categorized as either hospital- or community-acquired [ 15 ]. Hospital-acquired bacteremia was defined as the bacteremia diagnosed ≥48 hours after hospital admission [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…We recently reviewed peer-reviewed literature published between 2000 and 2015 and found only seven studies that examined changes in drug resistance in GNB HAIs [19-25]. Although one recently published study described an association between multidrug resistance and history of GNB bloodstream infections [26], the primary objective of the study was to measure costs associated with multidrug resistance rather than to focus on recurrent infections.…”
Section: Introductionmentioning
confidence: 99%